Environmental change in Lesotho an analysis of the causes and consequences of land-use change in the lowland region - Maro, Pendo (Springer Verlag, 2011)
The aim of this book is to identify and analyze the drivers of land-use change and the consequences of these changes on the livelihoods of rural land-users/managers. To accomplish this, a combination of tools from the social sciences and environmental fields were developed to identify causes and consequences of land-use change at selected levels, using a nested approach. These methods were then applied to a case study of villages in Maseru and Mohales Hoek districts in the Lowland region of Lesotho. Based on the research findings, key proximate drivers of land-use change in the Lowland villages were established. These were drought, lack of water, land mismanagement, HIV/AIDS and dependency syndrome. These were acted on by underlying and other drivers to bring about major changes in land-use. The book offers an understanding of the actions of local land-users and managers, and their responses to biophysical, social-political, environmental, HIV/AIDS and other stresses, giving an insight into a households decision-making behaviour, degree of vulnerability and hence their resilience and adaptive capabilities and mechanisms. This book is directed at the wide scientific and non-scientific audience including environmental and social science experts, researchers, decision-makers, and development/aid workers interested in understanding the intricate human-environment relationship as it relates to land-use change in a changing biophysical, socio-economic, political and institutional context, coupled by HIV/AIDS, changing demographics, local perceptions and what is termed here dependency syndrome.